Android quick APIs reference - Cinar, Onur (Apress, 2015)
This is a condensed code and APIs reference for the new Google Android 5.0 SDK. In this book you will find a software development kit and APIs reference that is concise, to the point and highly accessible. It is packed with useful information and is a must-have for any mobile or Android app developer or programmer. This resource provides a concise reference to the Android SDK and its APIs using the official Android Studio IDE. Topics include: a short introduction to the Android platform and its development environment; using the essential parts of Android applications, such as user interface, components, notifications, and resources; storing and accessing data using Android APIs; accessing device location and using device sensors; recording and playing back video and audio content; using the camera. --